Pedagogy Training Courses in the Mekong Delta: EFL Teachers' Satisfaction and Expectations - Le, Xuan Mai; Phan, Thanh Dat; Le, Thanh Thao (Faculty of Education and Teacher Training of IAIN Palopo, 2022)
This study investigates EFL teachers’ expectations and satisfaction with the teaching pedagogy training courses in the Mekong Delta. The study was conducted on teachers of English in the Mekong Delta of Vietnam, including 51 teachers answering the questionnaires, and six teachers were randomly invited for the interview. The results from the study revealed that the EFL teachers showed high expectations in the teaching pedagogy training courses. Significantly, the teachers expected to train on language teaching methodology, lesson planning, and technology the most. Additionally, most participants expressed high satisfaction with the teaching pedagogy training courses they had participated in. Remarkably, they were delighted with the program issues and academic aspects of training. The significant findings of this study were expected to contribute to the insightful understanding of EFL teachers’ needs and demands for training courses in general and suggestions for more effective training courses in the future.